The impact of drifting substorm-injected electrons on pulsating aurora initiation and intensification - Momberg, John C.; Jaynes, Allison N.; Chepuri, Sanjay N. F.; Leali, Alexis; Karl, Juliana A.; Troyer, Riley N. (Frontiers in Astronomy and Space Sciences, 2024)
Pulsating aurora, which consists of diffuse patches blinking on and off, is caused by pitch angle scattering of radiation belt electrons into the loss cone by lower-band chorus waves. Understanding the drivers of pulsating aurora is important as it is a long-lasting and widespread phenomenon, accounting for significant energy transfer from the solar wind into the ionosphere. Substorm injections, which transport electrons from the magnetotail into the inner magnetosphere, are one source of electrons in this region. Injections have been observed simultaneously with pulsating aurora during conjunctions between ground cameras and satellites. In addition, previous work has also shown that substorms can enhance chorus activity (the fundamental process that produces pulsating aurora), providing a mechanism linking substorms to pulsating aurora. To further study this connection, we used the Van Allen Probes and all-sky cameras to look at events where pulsating aurora and substorm injections were observed at different locations in Magnetic Local Time (MLT), rather than focusing only on conjunctions. To make this comparison, we calculated the drift rate of electrons originating from observed injections and projected their motion forward in time until their Magnetic Local Time was the same as the ground camera. When the electrons are located at the same MLT as the ground camera, the pulsating aurora they cause would most likely occur in the field of view of the camera. We compared the time drifting substorm-injected particles arrived at the MLT of the camera to when pulsating aurora was observed. We found several instances where the initiation or intensification of pulsating aurora was accompanied by the arrival of substorm-injected electrons. This observation gives further evidence that pulsating aurora can be enhanced by or occur after substorm injections.